Lived Experiences Of Adults Initially Sentenced To Life Without Option Of Parole As Juveniles And Their Transitioning Back Into The Community - Inegbenebor, Festus Osoiwan (My University, 2017)
At present, we know about the postincarceration experiences of individuals who were sentenced to prison for life as adults without the option of parole and transitioned back into the community, but we have little or no knowledge about the postincarceration experiences in transitioning back to the community of individuals who were teens at the time they were incarcerated and thereafter spent the rest of their teens, young adult years, and greater part of their adult lives in prison. This dissertation has two focuses: (a) those who are now adult but incarcerated as juveniles transitioning from prison into the community and (b) African Americans incarcerated as juveniles turned adult and their lived experiences in the community. It used an exploratory phenomenological method with a sample of eight African American individuals who were juvenile at the time of incarceration and are now residing in a large metropolitan city in the United States. A literature review revealed mass juvenile incarceration of African Americans and their difficult experiences and challenges while transitioning from prison to the community in regard to programs to reintegrate as adults, family and community support, need to expunge their juvenile criminal record, as well as employment, education, housing, and medical and mental healthcare needs. Findings from this exploratory study suggest that (a) juveniles commit crime because their cognitive ability is that of a child, meaning their brain is still developing; (b) poverty, and lack of employment, education, and family support are factors related to the inability of African American juveniles to integrate into the community; (c) education, job/employment programs, family, and other support systems are vital to former inmates post incarceration; (d) contrary to general belief that imprisonment does not serve a useful purpose, some participants concluded that they have benefitted immensely from imprisonment, especially in obtaining an education; (e) though it may be difficult, those who have been incarcerated for a very long period can still integrate into the community, be employed after their prison term, and become productive members of society. With regard to the implications for social work, this dissertation advances the idea that juveniles have the potential to grow, change, develop, and become more responsible, and as such, it is inhumane to send juveniles to life imprisonment. Imprisonment does not reduce crime; rather, rehabilitation does.
Keywords: Social service; Sentences (Criminal procedure)